The effect of a penile fracture on ejaculatory and erectile functions: A cross-sectional study - Can, Osman; Merder, Erkan; Canat, Halil Lütfi; Sabuncu, Kenan; Arıman, Ahmet; Altunrende, Fatih (Journal of Surgery and Medicine, 2021)
Background/Aim: There is not enough data in the literature about ejaculatory and erectile functions after a penile fracture. We aimed to report the post-fracture ejaculatory and erectile function change and their relationship with the psychological condition of the patient. Methods: We retrospectively evaluated 27 patients with a penile fracture who were treated surgically. Pre-fracture and post-fracture ejaculatory and erectile functions were evaluated with Intravaginal Ejaculation Latency Time (IELT) and International Index of Erectile Function (IIEF) questionnaires. The psychological conditions of the patients after the fracture were evaluated with the Beck depression score. Results: The mean IELT was increased after penile fracture (P=0.007). The post-fracture and pre-fracture IIEF scores were similar (P=0.062). There was a positive correlation between Beck depression score and post-fracture IELT (r=0.498; P=0.008). Conclusions: According to our results, ejaculation time was longer after penile fractures. It may be related to neurogenic damage due to trauma or the post-fracture psychological condition. However, larger studies with long-term outcomes may reveal the relationship more thoroughly.